Innate and Adaptive Immunity Synergize to Trigger Inflammation in the Mammary Gland. - Pascal Rainard; Patricia Cunha; Florence B Gilbert (PLoS ONE, 2016)
The mammary gland is able to detect and react to bacterial intrusion through innate immunity mechanisms, but mammary inflammation can also result from antigen-specific adaptive immunity. We postulated that innate and adaptive immune responses could synergize to trigger inflammation in the mammary gland. To test this hypothesis, we immunized cows with the model antigen ovalbumin and challenged the sensitized animals with either Escherichia coli lipopolysaccharide (LPS) as innate immunity agonist, ovalbumin as adaptive immunity agonist, or both agonists in three different udder quarters of lactating cows. There was a significant amplification of the initial milk leukocytosis in the quarters challenged with the two agonists compared to leukocytosis in quarters challenged with LPS or ovalbumin alone. This synergistic response occurred only with the cows that developed the ovalbumin-specific inflammatory response, and there were significant correlations between milk leukocytosis and production of IL-17A and IFN-γ in a whole-blood ovalbumin stimulation assay. The antigen-specific response induced substantial concentrations of IL-17A and IFN-γ in milk contrary to the response to LPS. Such a synergy at the onset of the reaction of the mammary gland suggests that induction of antigen-specific immune response with bacterial antigens could improve the initial immune response to infection, hence reducing the bacterial load and contributing to protection.